2020
DOI: 10.1021/acs.macromol.0c01450
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Dynamics of Janus Polynorbornenes: Glass Transitions and Nanophase Separation

Abstract: For the first time, dielectric and calorimetric investigations of a homologous series of Janus polynorbornenes with rigid main backbones and flexible −Si(OR) 3 side groups of differing length alkyl chains (R = propyl, butyl, hexyl, octyl, and decyl) is reported. Generally, this class of polymers has some potential for applications in the field of gas separation membranes. Two dielectrically active processes are observed at low temperatures, denoted as βand α-relaxation. The former can be assigned to localized … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
31
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 21 publications
(34 citation statements)
references
References 35 publications
3
31
0
Order By: Relevance
“…The appearance of a glass transition indicates a certain disorder present in the material where this disorder in the ILCn is due to nanophase separation between the flexible alkyl side chains and the rigid aromatic cores. Such a nanophase separation has been previously reported for other materials such as homologous series of polymers bearing different alkyl chain length, 29,30 other discotic liquid crystals 31−35 and for recently investigated ILCs. 15 Molecular Mobility.…”
Section: ■ Introductionsupporting
confidence: 71%
See 1 more Smart Citation
“…The appearance of a glass transition indicates a certain disorder present in the material where this disorder in the ILCn is due to nanophase separation between the flexible alkyl side chains and the rigid aromatic cores. Such a nanophase separation has been previously reported for other materials such as homologous series of polymers bearing different alkyl chain length, 29,30 other discotic liquid crystals 31−35 and for recently investigated ILCs. 15 Molecular Mobility.…”
Section: ■ Introductionsupporting
confidence: 71%
“…(b) d spacing values as function of the alkyl chain length. Spheres: ILC n ; open circles: HATn in the columnar phase taken from ref , Rhombus: Janus polynorbornenes (taken from ref ); up-pointing triangles: poly­( n -alkyl methacrylate); solid line: alkyl chain length in all trans configuration. Data for poly­( n -alkyl methacrylate) and all trans configuration of alkyl chains are taken from ref .…”
Section: Resultsmentioning
confidence: 99%
“…9 On the one hand, the former effect leads to nanophase separation, which has been confirmed by X-ray diffraction (XRD) for CLCs including HATn 9,10 as well as for different polymers possessing long n-alkyl side chains in their structure. [11][12][13][14] On the other hand, the favorable π-π interaction results in 1D high charge mobility along the column direction originating from the delocalization of π-electrons in the π-π stacked system of the HATn molecules in the Colh phase, where the flexible alkyl chains fill the intercolumnar area and are disordered among ordered columns of the cores (see Figure 1b). Majority of the studies reported in the literature regarding triphenylene-based DLCs HATn concentrate on the synthesis, the structure, the charge carrier mobility and the phase behavior of these materials.…”
Section: Introductionmentioning
confidence: 99%
“…It was proven that FSC enables to decouple the kinetics of degradation from other effects like melting, [37,38] the glass transition , [39][40][41] or the chain dynamics. [42,43]…”
Section: Fast Scanning Calorimetrymentioning
confidence: 99%
“…It should be noted that the influence of the polymerization mechanism (addition or metathesis) on the molecular mobility was discussed recently. [27] 2 | MATERIALS AND METHODS…”
mentioning
confidence: 99%